Determinan Aktivitas Fisik pada Aggregate Dewasa - Aulia Rahmi; Asniar Asniar; Teuku Tahlil (Jurnal Keperawatan Silampari, 2021)
This study aims to analyze the determination of physical activity in adult aggregates in Lhokseumawe City. The research design used was a descriptive correlation with a cross-sectional approach. The results showed that the majority of respondents were adults (26-35 years old) that is 61 people (62.9%), female 69 people (71.1%), higher education level 74 people (76.3%), working does not depend on time, namely, 36 people (37.1%), living in urban areas, namely 90 people (92.8%), and having a monthly income of <Rp 3,165,030, namely 69 people (71.1%). Variables related to physical activity were age (p=0.003), perceived benefits and barriers (p=0.024), and self-efficacy (p=0.000). The most dominant factor about physical activity in respondents was age, with an odds ratio of 4.622 (95% CI: 1.759-12.143). In conclusion, the most significant determinant of physical activity in the adult aggregate is age. Keywords: Aggregate Adults, Determinants of Physical Activity